2011
DOI: 10.1002/pip.1182
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic Degradation Rates—an Analytical Review

Abstract: As photovoltaic penetration of the power grid increases, accurate predictions of return on investment require accurate prediction of decreased power output over time. Degradation rates must be known in order to predict power delivery. This article reviews degradation rates of flatplate terrestrial modules and systems reported in published literature from field testing throughout the last 40 years. Nearly 2000 degradation rates, measured on individual modules or entire systems, have been assembled from the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
587
6
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,126 publications
(630 citation statements)
references
References 99 publications
25
587
6
12
Order By: Relevance
“…In contrast, the FA 0.83 Cs 0.17 Pb(I 0.6 Br 0.4 ) 3 cells only degrade by a few percent absolute efficiency over this time and then proceed to degrade at a much slower linear rate. [58,59] We note that we do not want to suggest that the FA 0.83 Cs 0.17 Pb(I 0.6 Br 0.4 ) 3 composition can specifically resist the degradation induced by the hydroscopic additives (i.e., Li-TFSI). But these results simply show that it is simply much more stable in general than the MAPbI x Cl 3-x composition.…”
Section: Doi: 101002/adma201604186mentioning
confidence: 96%
See 2 more Smart Citations
“…In contrast, the FA 0.83 Cs 0.17 Pb(I 0.6 Br 0.4 ) 3 cells only degrade by a few percent absolute efficiency over this time and then proceed to degrade at a much slower linear rate. [58,59] We note that we do not want to suggest that the FA 0.83 Cs 0.17 Pb(I 0.6 Br 0.4 ) 3 composition can specifically resist the degradation induced by the hydroscopic additives (i.e., Li-TFSI). But these results simply show that it is simply much more stable in general than the MAPbI x Cl 3-x composition.…”
Section: Doi: 101002/adma201604186mentioning
confidence: 96%
“…[59] However, when tested for over 20 years this degradation rate has been observed to increase. [59,62] Nevertheless, fitting the longterm decay of the degradation to a linear function would be consistent with how degradation is expected to proceed in commercial modules.…”
Section: Doi: 101002/adma201604186mentioning
confidence: 99%
See 1 more Smart Citation
“…The same author also mentioned that a fall of 0.4% in efficiency would be observed for each Celsius degree increase. However, other authors converged on a bit higher figure of 0.5% decrease (Jordan & Kurtz, 2013; Moharram, Abd-Elhady, Kandil, & El-Sherif, 2013). Also, studies conducted showed that the open-circuit voltage (Voc) changes much faster than the shortcircuit current (Isc) at respective rates of 0.37% and 0.05%; which inflicts a decrease of 0.5% in the maximum power point (MPP) per each temperature unit increase.…”
Section: Heat Effects On Pv Efficiencymentioning
confidence: 99%
“…Studies suggest that cells are subject to a degradation rate of about 0.5% per year. Furthermore, a cumulative degradation of 20% module is qualified as a complete failure of a solar module, though the assertion may be a subject of debates (Jordan & Kurtz, 2013). Even though ageing is natural, some factors are viewed as the catalysers of cells degradation.…”
Section: Manufacture Defects and Natural Causesmentioning
confidence: 99%